2011
DOI: 10.5047/eps.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Relation between similar aftershocks and ruptured asperity of a large inland earthquake: Example of the 2007 Noto Hanto earthquake

Abstract: We investigate spatial distribution of similar aftershocks of a large inland earthquake using waveform data obtained by a dense temporary seismic network. Similar earthquakes on the source fault are mainly located around the deeper edge of the major asperity. The cumulative slip estimated from the similar earthquakes ranges from 0.6 to 2.7 cm and coincides with the slip estimated from postseismic crustal movement observed by GPS. The slip velocity estimated from both the slip and the recurrence interval of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…They showed that similar aftershocks on the source fault are located mainly around the deeper edge of the major asperity. This result suggests that the afterslip area is spatially complementary to the asperity on the fault surface for inland earthquakes similar to large interplate earthquakes on the plate interface (Hiramatsu et al, 2011). However, to confirm this possibility, we must examine the existence and the spatial distribution of similar aftershocks for other large inland earthquakes.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…They showed that similar aftershocks on the source fault are located mainly around the deeper edge of the major asperity. This result suggests that the afterslip area is spatially complementary to the asperity on the fault surface for inland earthquakes similar to large interplate earthquakes on the plate interface (Hiramatsu et al, 2011). However, to confirm this possibility, we must examine the existence and the spatial distribution of similar aftershocks for other large inland earthquakes.…”
Section: Introductionmentioning
confidence: 93%
“…Our procedure to detect similar aftershocks follows that applied by Hiramatsu et al (2011). First, we select pairs of aftershocks of which the cross-correlation coefficients in a 10-s time window of 1-4 Hz band-pass filtered waveforms are greater than 0.95 at more than five stations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations